A Novel Method for Rapid Screening of Salmonidae Ingredients and Accurate Detection of Atlantic Salmon (Salmo salar) Simultaneously Using Duplex Real-Time PCR Coupled with Melting Curve Analysis - Wang, Shihui; Xiong, Xiong; Song, Hongwei; Wang, Tianlong; Li, Yi; Wang, Libin (Molecules (Basel, Switzerland), 2024)
The substitution of ingredients with Salmonidae, particularly Salmo salar, has led to widespread reports of financial losses and health risks globally, emphasizing the urgent need for the development of a rapid and precise method for species identification. The aim of the present study was to develop a novel method for the rapid screening of Salmonidae ingredients and the accurate detection of S. salar simultaneously using multiplex real-time PCR coupled with melting curve analysis. Specifically, primer sets specific for S. salar and Salmonidae were cross-confirmed. Moreover, the reaction system and conditions of a real-time duplex PCR were optimized, and the proposed methodology was verified, proving that the assay has good specificity and sensitivity. Clear and distinguishable melting peaks, with expected Tm values of around 80 °C (S. salar) and 84 °C (Salmonidae), were observed for twelve products, proving the presence of S. salar. However, four products were not derived from S. salar, but they could have belonged to another species within the Salmonidae family due to the presence of only one specific melting peak at a Tm value of about 84 °C. Therefore, the novel assay in the present study allows for the fast and accurate screening of Salmonidae ingredients and the detection of S. salar simultaneously.